What drives the community acceptance of onshore wind energy? Exploring the link between ownership, energy justice, and place in Scotland and Newfoundland ... - Hogan, Jessica (The University of St Andrews, 2024)
This thesis investigates the key factors influencing community acceptance of onshore wind energy, specifically examining the argument that fair involvement in decision-making and fair financial benefits are powerful determinants. The thesis examines this claim through various methodologies and across two different contexts: Scotland and Newfoundland. The initial papers, focusing on Scotland, employ quantitative surveys to investigate the significance of community ownership and energy justice in determining acceptance. By comparing communities which have different degrees of ownership, that is, community, shared, and private, the first paper highlights the characteristics of ownership that foster community acceptance. Notably, it emphasises the importance of fair involvement and financial benefits, providing evidence that a co-operative can achieve a similar degree of acceptance and energy justice as a fully community-owned project. Building on the findings of the first paper, the Scotland second paper ...